6.5: Factoring Special Forms
( \newcommand{\kernel}{\mathrm{null}\,}\)
In this section we revisit two special product forms that we learned in Chapter 5, the first of which was squaring a binomial.
Squaring a binomial
Here are two earlier rules for squaring a binomial.
- (a+b)2=a2+2ab+b2
- (a−b)2=a2−2ab+b2
Perfect Square Trinomials
To square a binomial such as (a+b)2, proceed as follows:
- Square the first term: a
- Multiply the first and second term, then double: 2ab
- Square the last term: b2
Example 6.5.1
Expand: (2x+3y)2
Solution
Using the pattern (a+b)2=a2+2ab+b2, we can expand (2x+3y)2 as follows:
(2x+3y)2=(2x)2+2(2x)(3y)+(3y)2=4x2+6xy+9y2
Note how we square the first and second terms, then produce the middle term of our answer by multiplying the first and second terms and doubling.
Exercise 6.5.1
Expand: (5a+2b)2
- Answer
-
25a2+20ab+4b2
Example 6.5.2
Expand: (3u2−5v2)2
Solution
Using the pattern (a−b)2=a2−2ab+b2, we can expand (3u2−5v2)2 as follows:
(3u2−5v2)2=(3u2)2−2(3u2)(5v2)+(5v2)2=9u4−30u2v2+25v4
Note that the sign of the middle term is negative this time. The first and last terms are still positive because we are squaring.
Exercise 6.5.2
Expand: (2s3−7t)2
- Answer
-
4s6−28s3t+49t2
Once you’ve squared a few binomials, it’s time to do all of the work in your head.
- Square the first term.
- Multiply the first and second term and double the result.
- Square the second term.
Example 6.5.3
Expand each of the following:
- (2y−3)2
- (4a−3b)2
- (x3+5)2
Solution
Using the pattern (a±b)2=a2±2ab+b2, we expand each binomially mentally, writing down the answer without any intermediate steps.
- (2y−3)2=4y2−12y+9
- (4a−3b)2=16a2−24ab+9b2
- (x3+5)2=x6+10x3+25
Exercise 6.5.3
Expand: (5x4−3)2
- Answer
-
25x8−30x4+9
Now, because factoring is “unmultiplying,” it should be a simple matter to reverse the process of Example 6.5.3.
Example 6.5.4
Factor each of the following trinomials:
- 4y2−12y+9
- 16a2−24ab+9b2
- x6+10x3+25
Solution
Because of the work already done in Example 6.5.3, it is a simple task to factor each of these trinomials.
- 4y2−12y+9=(2y−3)2
- 16a2−24ab+9b2=(4a−3b)2
- x6+10x3+25=(x3+5)
Exercise 6.5.4
Factor: 25x8−30x4+9
- Answer
-
(5x4−3)2
Each of the trinomials in Example 6.5.4 is an example of a perfect square trinomial.
Perfect square trinomial
If a trinomial a2+2ab+b2 is the square of a binomial, as in (a+b)2, then the trinomial is called a perfect square trinomial.
So, how does one recognize a perfect square trinomial? If the first and last terms of a trinomial are perfect squares, then you should suspect that you may be dealing with a perfect square trinomial. However, you also have to have the correct middle term in order to have a perfect square trinomial.
n | n2 |
---|---|
1 | 1 |
2 | 4 |
3 | 9 |
4 | 16 |
5 | 25 |
6 | 36 |
7 | 49 |
8 | 64 |
9 | 81 |
10 | 100 |
11 | 121 |
12 | 144 |
13 | 169 |
14 | 196 |
15 | 225 |
16 | 256 |
17 | 289 |
18 | 324 |
19 | 361 |
20 | 400 |
21 | 441 |
22 | 484 |
23 | 529 |
24 | 576 |
25 | 625 |
Example 6.5.5
Factor each of the following trinomials:
- 9x2−42x+49
- 49a2+70ab+25b2
- 4x2−37x+9
Solution
Note that the first and last terms of each trinomial are perfect squares.
- In the trinomial 9x2−42x+49, note that (3x)2=9x2 and 72=49. Hence, the first and last terms are perfect squares. Taking the square roots, we suspect that 9x2−42x+49 factors as follows: 9x2−42x+49?=(3x−7)2However, we must check to see if the middle term is correct. Multiply 3x and 7, then double: 2(3x)(7)=42x. Thus, the middle term is correct and therefore 9x2−42x+49=(3x−7)2
- In the trinomial 49a2+70ab+25b2, note that (7a)2=49a2 and (5b)2=25b2. Hence, the first and last terms are perfect squares. Taking the square roots, we suspect that 49a2+70ab+25b2 factors as follows: 49a2+70ab+25b2?=(7a+5b)2However, we must check to see if the middle term is correct. Multiply 7a and 5b, then double: 2(7a)(5b)=70ab. Thus, the middle term is correct and therefore 49a2+70ab+25b2=(7a+5b)2
- In the trinomial 4x2−37x+9, note that (2x)2=4x2 and (3)2=9. Hence, the first and last terms are perfect squares. Taking the square roots, we suspect that 4x2−37x+9 factors as follows: 4x2−37x+9?=(2x−3)2
However, we must check to see if the middle term is correct. Multiply 2x and 3, then double: 2(2x)(3)=12x. However, this is not the middle term of 4x2−37x+9, so this factorization is incorrect! We must find another way to factor this trinomial.
Comparing 4x2−37x+9 with ax2+bx+c, we need a pair of integers whose product is ac=36 and whose sum is b=−37. The integer pair −1 and −36 comes to mind. Replace the middle term as a sum of like terms using this ordered pair.
4x2−37x+9=4x2−x−36x+9−37x=−x−36x=x(4x−1)−9(4x−1)Factor by grouping=(x−9)(4x−1)Factor out 4x−1
This example clearly demonstrates how important it is to check the middle term.
Exercise 6.5.5
Factor: 16x2+72x+81
- Answer
-
(4x+9)2
Remember the first rule of factoring!
Example 6.5.6
Factor each of the following trinomials:
- 2x3y+12x2y2+18xy3
- −4x5+32x4−64x3
Solution
Remember, first factor out the GCF.
- In the trinomial 2x3y+12x2y2+18xy3, we note that the GCF of 2x3y, 12x2y2, and 18xy3 is 2xy. We first factor out 2xy.2x3y+12x2y2+18xy3=2xy(x2+6xy+9y2)We now note that the first and last terms of the resulting trinomial factor are perfect squares, so we take their square roots and factors as follows.=2xy(x+3y)2Of course, the last factorization is correct only if the middle term is correct. Because 2(x)(3y)=6xy matches the middle term of x2+6xy+9y2, we do have a perfect square trinomial and our result is correct.
- In the trinomial −4x5+32x4−64x3, we note that the GCF of 4x5, 32x4, and 64x3 is 4x3. We first factor out 4x3.−4x5+32x4−64x3=4x3(−x2+8x−16) However, the first and third terms of −x2+8x−16 are negative, and thus are not perfect squares. Let’s begin again, this time factoring out −4x3.−4x5+32x4−64x3=−4x3(x2−8x+16) This time the first and third terms of x2−8x+16 are perfect squares. We take their square roots and write: =−4x3(x−4)2 Again, this last factorization is correct only if the middle term is correct. Because 2(x)(4)=8x, we do have a perfect square trinomial and our result is correct.
Exercise 6.5.6
Factor: −4x3−24x2−36x
- Answer
-
−4x(x+3)2
The Difference of Squares
The second special product form we learned in Chapter 5 was the difference of squares.
The difference of squares
Here is the difference of squares rule.(a+b)(a−b)=a2−b2
If you are multiplying two binomials which have the exact same terms in the “First” positions and the exact same terms in the “Last” positions, but one set is separated by a plus sign while the other set is separated by a minus sign, then multiply as follows:
- Square the first term: a2
- Square the second term: b2
- Place a minus sign between the two squares.
Example 6.5.7
Expand each of the following:
- (3x+5)(3x−5)
- (a3−2b3)(a3+2b3)
Solution
We apply the difference of squares pattern to expand each of the given problems.
- In (3x+5)(3x−5), we have the exact same terms in the “First” and “Last” positions, with the first set separated by a plus sign and the second set separated by a minus sign.
- Square the first term: (3x)2=9x2
- Square the second term: 52=25
- Place a minus sign between the two squares.
Hence:(3x+5)(3x−5)=9x2−25
- In (a3−2b3)(a3+2b3), we have the exact same terms in the “First” and “Last” positions, with the first set separated by a minus sign and the second set separated by a plus sign.
- Square the first term: (a3)2=a6
- Square the second term: (2b3)2=4b6
- Place a minus sign between the two squares.
Hence:(a3−2b3)(a3+2b3)=a6−4b6
Exercise 6.5.7
Expand: (4x−3y)(4x+3y)
- Answer
-
16x2−9y2
Because factoring is “unmultiplying,” is should be a simple matter to reverse the process of Example 6.5.7.
Example 6.5.8
Factor each of the following:
- 9x2−25
- a6−4b6
Solution
Because of the work already done in Example 6.5.7, it is a simple matter to factor (or “unmultiply”) each of these problems.
- 9x2−25=(3x+5)(3x−5)
- a6−4b6=(a3−2b3)(a3+2b3)
In each case, note how we took the square roots of each term, then separated one set with a plus sign and the other with a minus sign. Because of the commutative property of multiplication, it does not matter which one you make plus and which one you make minus.
Exercise 6.5.8
Factor: 81x2−49
- Answer
-
(9x+7)(9x−7)
Always remember the first rule of factoring.
Example 6.5.9
Factor: x3−9x
Solution
In x3−9x, the GCF of x3 and 9x is x. Factor out x. x3−9x=x(x2−9)Note that x2−9 is now the difference of two perfect squares. Take the square roots of x2 and 9, which are x and 3, then separate one set with a plus sign and the other set with a minus sign.
=x(x+3)(x−3)
Exercise 6.5.9
Factor: 4x4−16x2
- Answer
-
4x2(x+2)(x−2)
Factoring Completely
Sometimes after one pass at factoring, factors remain that can be factored further. You must continue to factor in this case.
Example 6.5.10
Factor: x4−16
Solution
In x4−16, we have the difference of two squares: (x2)2=x4 and 42=16. First, we take the square roots, then separate one set with a plus sign and the other set with a minus sign. x4−16=(x2+4)(x2−4)Note that x2+4 is the sum of two squares and does not factor further. However, x2−4 is the difference of two squares. Take the square roots, x and 2, then separate one set with a plus sign and the other set with a minus sign.
=(x2+4)(x+2)(x−2)Done. We cannot factor further.
Exercise 6.5.10
Factor: x4−81
- Answer
-
(x2+9)(x+3)(x−3)
Nonlinear Equations Revisited
Remember, if an equation is nonlinear, the first step is to make one side equal to zero by moving all terms to one side of the equation. Once you’ve completed this important first step, factor and apply the zero product property to find the solutions.
Example 6.5.11
Solve for x: 25x2=169
Solution
Make one side equal to zero, factor, then apply the zero product property.
25x2=169Original equation.25x2−169=0Subtract 169 from both sides.
Note that we have two perfect squares separated by a minus sign. This is the difference of squares pattern. Take the square roots, making one term plus and one term minus.
(5x+13)(5x−13)=0Use difference of squares to factor.
Use the zero product property to complete the solution, setting each factor equal to zero and solving the resulting equations.
5x+13=0x=−135
or
5x−13=0x=135
Hence, the solutions of 25x2=169 are x=−13/5 and x=13/5. We encourage readers to check each of these solutions.
Exercise 6.5.11
Solve for x: 16x2=121
- Answer
-
−11/4, 11/4
Example 6.5.12
Solve for x: 49x2+81=126x
Solution
Make one side equal to zero, factor, then apply the zero product property.
49x2+81x=126xOriginal equation.49x2−126x+81=0Subtract 126x from both sides.
Note that the first and last terms of the trinomial are perfect squares. Hence, it make sense to try and factor as a perfect square trinomial, taking the square roots of the first and last terms.
(7x−9)2=0Factor as a perfect square trinomial.
Of course, be sure to check the middle term. Because −2(7x)(9)=−126x, the middle term is correct. Because (7x−9)2=(7x−9)(7x−9), we can use the zero product property to set each factor equal to zero and solve the resulting equations.
7x−9=0x=97
or
7x−9=0x=97
Hence, the only solution of 49x2+81=126x is x=9/7. We encourage readers to check this solution.
Note
One can also argue that the only number whose square is zero is the number zero. Hence, one can go directly from (7x−9)2=0 to 7x−9=0. Hence, the only solution of 49x2+81=126x is x=9/7.
Exercise 6.5.12
Solve for x: 25x2=80x−64
- Answer
-
8/5
Example 6.5.13
Solve for x: 2x3+3x2=50x+75
Solution
Make one side equal to zero, factor, then apply the zero product property.
2x3+3x2=50x+75Original equation.2x3+3x2−50x−75=0Make one side zero.
This is a four-term expression, so we try factoring by grouping. Factor x2 out of the first two terms, and −25 out of the second two terms.
x2(2x+3)−25(2x+3)=0Factor by grouping(x2−25)(2x+3)=0Factor out 2x+3
Complete the factorization by using the difference of squares to factor x2−25.
(x+5)(x−5)(2x+3)=0Use difference of squares to factor.
Finally, use the zero product property. Set each factor equal to zero and solve for x.
x+5=0x=−5
or
x−5=0x=5
or
2x+3=0x=−32
Hence, the solutions of 2x3+3x2=50x+75 are x=−5, x=5, and x=−3/2. We encourage readers to check each of these solutions.
Exercise 6.5.13
Solve for x: 5x3+36=x2+180x
- Answer
-
−6, 6, 1/5
Let’s solve another nonlinear equation, matching the algebraic and graphical solutions.
Example 6.5.14
Solve the equation x^3 =4x, both algebraically and graphically, then compare your answers.
Solution
Note that we have a power of x larger than one, so the equation x^3 =4x is nonlinear. Make one side zero and factor.
\begin{align*} x^3 &= 4x \quad \color {Red} \text {Original equation.}\\ x^3-4x &= 0 \quad \color {Red} \text {Nonlinear. Make one side zero. }\\ x(x^2-4) &=0 \quad \color {Red} \text {Factor out GCF.}\\ x(x+2)(x-2) &= 0 \quad \color {Red} \text {Apply difference of squares.} \end{align*} \nonumber
Note that we now have a product of three factors that equals zero. The zero product property says that at least one of these factors must equal zero.
\begin{align*} x &= 0 \end{align*} \nonumber
or
\begin{align*} x+2 &= 0 \\ x &= -2 \end{align*} \nonumber
or
\begin{align*} x-2 &= 0 \\ x &= 2 \end{align*} \nonumber
Hence, the solutions of x^3 =4x are x = 0, x = −2, and x = 2.
Graphical solution
Load y = x^3 and y =4x into \mathbb{Y1} and \mathbb{Y2 }in the Y= menu of your calculator. Select 6:ZStandard from the ZOOM menu to produce the graph in Figure \PageIndex{1}.
Although the image in Figure \PageIndex{1} shows all three points of intersection, adjusting the WINDOW parameters as shown in Figure \PageIndex{2}, then pressing the GRAPH button will produce a nicer view of the points of intersection, as shown in the figure on the right in Figures \PageIndex{2}.


Use the 5:intersect tool from the CALC menu to find the three points of intersection. Press the ENTER key in response to “First curve,” then press ENTER again in response to “Second curve,” then use the left-arrow key to move your cursor close to the leftmost point of intersection and press ENTER in response to “Guess.” The result is shown in the first image on the left in Figure \PageIndex{3}. Repeat the process to find the remaining points of intersection. The results are shown in the last two images in Figure \PageIndex{3}.

Thus, the graphical solutions are x =−2, x = 0, and x = 2.
Reporting the solution on your homework:
Duplicate the image in your calculator’s viewing window on your homework page. Use a ruler to draw all lines, but freehand any curves.
- Label the horizontal and vertical axes with x and y, respectively (see Figure \PageIndex{4}).
- Place your WINDOW parametersat the end of each axis (see Figure \PageIndex{4}).
- Label the graph with its equation (see Figure \PageIndex{4}).
- Drop dashed vertical lines through each x-intercept. Shade and label the x-values of the points where the dashed vertical line crosses the x-axis. These are the solutions of the equation x^3 = 4x (see Figure \PageIndex{4}).

Finally, note that the graphical solutions x = −2, x = 0, and x = 2 match our algebraic solutions exactly.
Exercise \PageIndex{14}
Solve the equation x^3 = 16x both algebraically and graphically, then compare your answers.
- Answer
-
−4, 0, 4